Clinicopathologic Analyses of Failed Endothelial Keratoplasty (the Clinical Cases) - Yu. N. Yusef; N. V. Fisenko; T. A. Demura; G. A. Osipyan (Oftalʹmologiâ, 2023)
Purpose: To evaluate the clinicopathologic features of failed endothelial keratoplasty. Methods. In this study 11 patients (11 eyes) with recurrence of bullous keratopathy (BK) were included. Group 1 consisted of 4 patients who underwent repeat Descemet Stripping Automated Endothelial Keratoplasty (DSAEK), group 2 included 7 patients who underwent penetrating keratoplasty (PK) after failed Descemet Membrane Endothelial Keratoplasty (DMEK). Preoperative anterior segment optical coherence tomography (OCT), RTVue-100, Optovue, USA, was performed. Intraoperatively aqueous humour (AqH) samples were collected for multiplex cytokine analysis. During keratoplasty failed grafts/corneal buttons were obtained and then investigated histologically (hematoxylin/eosin staining, primary antibodies to pancytokeratin, vimentin, collagen III). Results. Recurrence of BK in all clinical cases manifests by the increase of inflammatory factors in AqH, corneal edema, neovascularization and remodeling to fibrosis. Glaucoma may induce DMEK/ DSAEK graft failure due to chronic local inflammation. In the clinical cases recurrence of BK was caused by peripheral and central graft detachment, rebubbling, graft upside-down orientation and donor corneal genetic disorders. Conclusions. Chronic local inflammation (including corneal morphological changes) in patients with BK recurrence is an indication for reoperation. The modification of keratoplasty — DMEK/DSAEK/PK — is determined according to slit-lamp and OCT images of the cornea. High-level risk of immune reaction (especially in cases of three and more times repeated keratolasty) is the reason for systemic corticosteroid and, sometimes, cytostatic therapy.